1989
DOI: 10.1080/02827588909382579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fertilizer nitrogen accumulation in Pinus sylvestris trees and retention in soil by 15N recovery technique

Abstract: Assessment of fertilizer nitrogen accumulation in Pinus sylvestris trees and retention in soil by 15 N recovery technique. Accepted Jan. 9, 1989. Scand. J. For. Res. 4:427-442, 1989.The distribution and quantitative recovery of fertilizer N were determined in three 29-to 43-year-old stands of Scots pine, located in western Uppland, Central Sweden. The experimental technique involved was based on the use of 15 N-labelled fertilizer materials and non-trenched microplots of special design. The standard dose of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Vol. 30, 2000 1990; Nômmik and Larsson 1989). Contrasting to the finding in Koopmans et al (1996), who studied sites with high rates of N deposition, the retention of 15 N in the organic layers (primarily humus layer, see the materials and methods section) in this study was quite stable as no obvious decrease of 15 N recovery rate in the soil was found.…”
Section: Discussioncontrasting
confidence: 84%
“…Vol. 30, 2000 1990; Nômmik and Larsson 1989). Contrasting to the finding in Koopmans et al (1996), who studied sites with high rates of N deposition, the retention of 15 N in the organic layers (primarily humus layer, see the materials and methods section) in this study was quite stable as no obvious decrease of 15 N recovery rate in the soil was found.…”
Section: Discussioncontrasting
confidence: 84%
“…15 N seedling −1 ) adapted in this study is adequate to study current uptake and retranslocation processes and has been successfully implemented in other studies (Amponsah et al, 2004;Mead and Preston, 1994;Preston and Mead, 1994). Additionally, Nômmik and Larson (1989) found no significant differences in 15 N recovery between split doses vs. a single application. Chelated micronutrients (EDTA 42% and DTPA 13%) were applied at the rate of 0.03 g L −1 to prevent any deficiency (Salifu and Timmer, 2003).…”
Section: Plant Materials and Growing Conditionsmentioning
confidence: 77%
“…Work in an old-growth temperate evergreen mixed-angiosperm forest in southern Chile indicates that the transformation of applied inorganic N was dominated by rapid assimilation and turnover through microbial biomass in the short term (weeks), and transfer from microbial biomass into nitrogen-conserving plant (and to a lesser extent soil organic matter) pools in the long term (years) (Perakis and Hedin, 2001). Such processes (whether the soil or plant biomass is the main sink for the applied-N) result in efficient long-term retention of nitrogen in forest ecosystems, with the bulk of residual fertilizer N generally found in the organic and upper mineral horizons, in both short-and longer-term studies (e.g., Mead and Pritchett, 1975;Nômmik and Larsson, 1989;Preston and Mead, 1994).…”
Section: Labelled-urea Recovery Over Timementioning
confidence: 98%